2002
DOI: 10.1074/jbc.m110686200
|View full text |Cite
|
Sign up to set email alerts
|

The Fission Yeast ES2 Homologue, Bis1, Interacts with the Ish1 Stress-responsive Nuclear Envelope Protein

Abstract: In fission yeast, nutrient starvation induces physiological, biochemical, and morphological changes that enable survival. Collectively these changes are referred to as stationary phase. We have used a green fluorescent protein random insertional mutagenesis system to isolate two novel stress-response proteins required in stationary phase. Ish1 is a nuclear envelope protein that is present throughout the cell cycle and whose expression is increased in response to stresses such as glucose and nitrogen starvation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 49 publications
4
34
0
1
Order By: Relevance
“…GFPtagged ESS-2 was primarily localized to the nucleus, with occasional detection of one or a few bright nuclear puncta ( Figure 5F). Similar nuclear puncta have also been reported for the fission yeast homolog, Bis1 (Taricani et al 2002). Expression of cDNA isolated from ess-2(ok3569) did not rescue ess-2(tm4246).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…GFPtagged ESS-2 was primarily localized to the nucleus, with occasional detection of one or a few bright nuclear puncta ( Figure 5F). Similar nuclear puncta have also been reported for the fission yeast homolog, Bis1 (Taricani et al 2002). Expression of cDNA isolated from ess-2(ok3569) did not rescue ess-2(tm4246).…”
supporting
confidence: 52%
“…The fission yeast ortholog of ES2, Bis1, was found as an interacting protein to a stress-response nuclear envelope protein Ish1 (induced in stationary phase 1) and plays a role in viability in the stationary phase (Taricani et al 2002). Human ES2/DGCR14 is highly expressed in heart, brain, and skeletal muscle and is located in the common chromosome region on 22q11.2 deleted in patients with DiGeorge syndrome and velocardiofacial syndrome Rizzu et al 1996;Gong et al 1997).…”
Section: Ess-2 Regulates Mrna Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…To construct pepe1-GFP, the epe1 ϩ open reading frame was PCR amplified from genomic DNA with primers that incorporate SalI and AseI restriction sites (5Ј-ACGCGTCGACAGACTAGCACCTCTGGACCGAAG C-3Ј and 5Ј-ACGCATTAATATGGATTCCTGGCTTGAATACG-3Ј). A SalI-AseI fragment of the PCR fragment was then ligated to a SalI-NdeI fragment of pRep1-GFP (39). Diploid strains were constructed by mating AP161 and AP182 (epe1 ϩ /epe1 ϩ ), AP161 and AP2002 (epe1 ϩ /epe1-1), and AP2002 and AP2003 (epe1-1/epe1-1).…”
Section: Methodsmentioning
confidence: 99%
“…I identified several known transcriptional coregulators (see Table S1 in the supplemental (20,21), which is characterized by various defects of the heart, thymus, and parathyroid gland (22). DGCR14 is a nuclear protein with a coiled-coil domain (21) that is conserved in lower species, including Drosophila melanogaster (23), Caenorhabditis elegans (24), and yeast (25). Although recent studies showed that DGCR14/ES2 associates with other nuclear proteins (26) or the splicing complex (27), the role of DGCR14 in T lymphocytes is not fully understood.…”
Section: Dgcr14mentioning
confidence: 99%